A supplier selection model using group decision-making systems under multiple criteria considering regret factor. (7th August 2020) - Azadfallah, Mohammad
In the current literature, supplier selection problem is defined as "the process by which companies identify, evaluate and choose the supplier to become part of their supply chain." Indeed, supplier selection is a multi-criteria decision-making (MCDM) problem affected by several conflicting factors (i.e., price, delivery time, etc.). However, some authors claim that this problem is typically a multi-criteria group decision-making (MCGDM) problem. On the other side, incorporating behavioural aspects, such as feelings of regret and rejoicing, into MCDM model intriguing area has been introduced. Therefore, the question typically posed is whether emotional feelings (particularly, regret factor) can be modelled systematically for an established MCGDM model? In this paper, we propose a new TOPSIS-based algorithm for determining regret measure in the group decision-making process. So, in the first step, the proposed method is used, the results of this step are inputs for the existing group TOPSIS methodology in the next step. Finally, to clarify our proposed algorithm, a numerical example involves a multi-criteria supplier selection problem in a supply chain context is discussed. The results indicate that the accuracy of the decision has been increased by considering the regret factors.